A Case Report of Long-Term Survival following Hepatic Arterial Infusion of L-Folinic Acid Modulated 5-Fluorouracil Combined with Intravenous Irinotecan and Cetuximab Followed by Hepatectomy in a Patient with Initially Unresectable Colorectal Liver Metastases - Kobe Van Bael; Yanina Jansen; Teofila Seremet; Benedikt Engels; Georges Delvaux; Bart Neyns (Case Reports in Oncological Medicine)
A 43-year-old women admitted to our hospital for weight loss, anorexia, and abdominal pain was diagnosed with sigmoid neoplasm and multiple bilobar liver metastases. This patient received six cycles of systemic FOLFOX prior to a laparoscopically assisted anterior resection of the rectosigmoid for a poorly differentiated invasive adenocarcinoma T2N2M1, K-RAS negative (wild type). Hepatic arterial infusion (HAI) of L-folinic acid modulated 5-fluorouracil (LV/5-FU) with intravenous (iv) irinotecan (FOLFIRI) and cetuximab as adjuvant therapy resulted in a complete metabolic response (CR) with CEA normalization. A right hepatectomy extended to segment IV was performed resulting in (FDG-)PET negative remission for 7 months. Solitary intrahepatic recurrence was effectively managed by local radiofrequent ablation following 6c FOLFIRI plus cetuximab iv. Multiple lung lesions and recurrence of pulmonary and local lymph node metastases were successfully treated with fractionated stereotactic radiotherapy (50 Gy) and iv LV/5-FU/oxaliplatin (FOLFOX) plus cetuximab finally switched to panitumumab with CR as a result. At present the patient is in persistent complete remission of her stage IV colorectal cancer, more than 5 years after initial diagnosis of the advanced disease. Multidisciplinary treatment with HAI of chemotherapy (LV/5-FU + CPT-11) plus EGFR-inhibitor can achieve CR of complex unresectable LM and can even result in hepatectomy with possible long-term survival.